Risk Factors for Community-Associated Clostridium difficile Infection in Adults: A Case-Control Study. (26th October 2017) - Guh, Alice Y; Adkins, Susan Hocevar; Li, Qunna; Bulens, Sandra N; Farley, Monica M; Smith, Zirka; Holzbauer, Stacy M; Whitten, Tory; Phipps, Erin C; Hancock, Emily B; Dumyati, Ghinwa; Concannon, Cathleen; et al.
Abstract: Background: An increasing proportion of Clostridium difficile infections (CDI) in the United States are community-associated (CA). We conducted a case-control study to identify CA-CDI risk factors. Methods: We enrolled participants from 10 US sites during October 2014–March 2015. Case patients were defined as persons age ≥18 years with a positive C. difficile specimen collected as an outpatient or within 3 days of hospitalization who had no admission to a health care facility in the prior 12 weeks and no prior CDI diagnosis. Each case patient was matched to one control (persons without CDI). Participants were interviewed about relevant exposures; multivariate conditional logistic regression was performed. Results: Of 226 pairs, 70.4% were female and 52.2% were ≥60 years old. More case patients than controls had prior outpatient health care (82.1% vs 57.9%; P < .0001) and antibiotic (62.2% vs 10.3%; P < .0001) exposures. In multivariate analysis, antibiotic exposure—that is, cephalosporin (adjusted matched odds ratio [AmOR], 19.02; 95% CI, 1.13–321.39), clindamycin (AmOR, 35.31; 95% CI, 4.01–311.14), fluoroquinolone (AmOR, 30.71; 95% CI, 2.77–340.05) and beta-lactam and/or beta-lactamase inhibitor combination (AmOR, 9.87; 95% CI, 2.76–340.05), —emergency department visit (AmOR, 17.37; 95% CI, 1.99–151.22), white race (AmOR 7.67; 95% CI, 2.34–25.20), cardiac disease (AmOR, 4.87; 95% CI, 1.20–19.80), chronic kidney disease (AmOR, 12.12; 95% CI, 1.24–118.89), and inflammatory bowel disease (AmOR, 5.13; 95% CI, 1.27–20.79) were associated with CA-CDI. Conclusions: Antibiotics remain an important risk factor for CA-CDI, underscoring the importance of appropriate outpatient prescribing. Emergency departments might be an environmental source of CDI; further investigation of their contribution to CDI transmission is needed.